ASPEK SOSIO-NATURAL HALAMAN SEKOLAH: MODEL EVALUASI ERINTEGRASI BIOEKOLOGI DAN PREFERENSI LINGKUNGAN DALAM EKOSISTEM URBAN - Surata, Sang Putu Kaler; Suda, I Ketut; Sudiana, I Made (Bumi Lestari; Vol 11 No 2 (2011), 2011)
School yards are a part of a few green open areas in urban environment. Therefore, school yard has important role for urban ecosystem. The goal of this research is to compare bioecological condition among elementary, middle and high schools and analyse the level of relationship among bioecological aspects, students and teachers preferencies toward their school yards. We have conducted research in 2008 which involved 20 elementary, 8 middle and 8 high schools at Denpasar Bali. Those schools were devided to be two groups: A (we observed their shool yards and have taken survey for students and teachers) and B (only taken survey to students and teachers). Results showed that percentage of oppened yard toward total areas of elementary school (46,5±17,1%) higher than middle school (38,8 ±15,5%) and high school (37,5±9,6%). Also the proportion of school garden in elementary school (30,2±20,3%) nearly twice higher than middle school (18,8± 6,3%) and high school (20,0±8,2%). Environmental preferencies of majority sample (>80%) were higher than point 4 of 7 Likert scales. Its mean, they tend to give positive image both artistic (beautiful, green, fresh, healty, happy and wide) and the ecological roles of school yard (rain water catchment, pollution absorbtion, animal habitat, oxygen supply, opennes toward sunlight and plant biodiversity). While plot of factor analysis showed that bioecological scores located in the same field with environmental preferencies of samples from group B. Thus the model of integration between environmental preferencies and bioecological evaluation able to give a new perspective of school yard as a socio-natural unit. Its not only important for ecosystem but also for human well-being. Thus we suggested to apply socio-natural approaches, mainly through enggaging non-owner communities in rating certain of the urban ecosistem.
Keywords: bioecology; environmental preferencies; school yard; sosio-natural unit